Wireless Sensor System and Internet Of Things for Environment Censoring - Singh, Teg; Singh, Jagvinder (Gyan Management Journal, 2017)
Wireless communication system enables the development of wireless sensor networks(WSNs). This paper discuss the wireless sensor network and JOT (Internet of Things) The best way of integrating WSN and JOT for environmental monitoring are analized. The sensor node is developed to monitor environmental parameters such as temperature and humidity. Wireless communication system responsibility to the sensor concept applied to a scaled industrial process where temperature variable were used. The sensor SHT75 to sense the temperature and humidity of the environmental with gateway, LCD to display information are interfaced with MSP430 microcontroller the monitoring process was performed with a SCAD A system.